O Museu da Emigração e os ''Brasileiros'' do Rio : o público e o privado na construção da modernidade em Portugal - Monteiro, Miguel (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This article presents the path of an emigrant from Fafe in Rio de Janeiro as pretext for introducing the Museum of Emigration, Communities and Luso-Descendants, created in Fafe.